God the 'Mother' and the Imagery of 'Womb' In the Writings of St. Teresa of Avila - Thattamparampil, Savia (Asian Horizons, 2009)
Savia Thattamparampil argues that a feminine perspective of God can contribute a new dimension to our present understanding of Divinity which has a macho touch to say the minimum. She opines that for a creator-sustainer God the title mother is more apt and fitting than the title Father. She claims that the rediscovery. projection and promotion of the feminine nature of the Holy Spirit can bring about a better balance to the Trinitarian concept of God in Christianity. She explores the contributions of St. Teresa of Avila to resuscitate a God with feminine face. heart. and womb.